Improvements of Prosthetic Limb Design: Cooling and Pressure Reduction in a Socket - Tomanec, Filip; Rusnakova, Sona; Zaludek, Milan (Manufacturing Technology Journal, 2017)
Although important improvements of prosthetic sockets has been implemented another investigation has been done also by solving problems with inadequate stump heating and from that resulting excessive sweating of limb. This phenomenon is further associated with leg volume changes. Therefore for realization of this research the model of prosthetic limb was created with socket that further addresses these issues of artificial limb. Throw the application of holes and tightening bells the pressure to remaining stump decreased and at the same time the heating of limb is lower. These results indicate that the implementation of these design modification will improve the comfort and fit of prosthetic devices in future.
Keywords: Prosthesis; artificial limb; socket; design; stump